2005
DOI: 10.1007/s11124-005-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemically deposited Ni-W-B coatings: Composition, structure, and properties

Abstract: The effect of temperature and solution components of the chemical catalytic reduction on the composition of Ni-W-B alloy coatings is studied. The x-ray photoelectron spectroscopy in combination with the layer-by-layer profile analysis is used to determine the chemical state of elements and the composition of surface and bulk layers of the coatings containing 28 and 1.8 wt % (10 and 12 at. %) tungsten and boron, respectively. The surface of such coatings is shown to contain up to 90 and 80 at. % reduced nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 4 publications
6
24
0
1
Order By: Relevance
“…While there have been a numerous studies on hypophosphite-reduced electroless plating, researches on boron, one of the most important amorphous elements, containing deposits has shifted. Sodium borohydride or dimethylamine borane (DMAB) is widely used as reducing agents to attain electroless Ni-B deposits [4], [5] Ni-W-B deposition which provides higher wear resistance can be procured by adding sodium tungstate to the electroless Ni-B bath [6].…”
Section: Introductionmentioning
confidence: 99%
“…While there have been a numerous studies on hypophosphite-reduced electroless plating, researches on boron, one of the most important amorphous elements, containing deposits has shifted. Sodium borohydride or dimethylamine borane (DMAB) is widely used as reducing agents to attain electroless Ni-B deposits [4], [5] Ni-W-B deposition which provides higher wear resistance can be procured by adding sodium tungstate to the electroless Ni-B bath [6].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance characteristics of the Ni-B coatings, different methods are applied, like applying heat treatments, adding different hard particles like WC, SiC, BN etc. or a second metal element such as copper, tungsten, cobalt, or molybdenum into the coating (Ref [10][11][12]. In earlier studies, it is concluded that this change in structure causes an increase in hardness and wear resistance because of the formation of grains and hard precipitations (Ref [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the major nickel borides formed during the heat treatments might have prevented the formation of the B-W bond. 9,15 In other words, the quantity of the boron in the coating was high enough to prevent the formation of Ni-W compounds in the structure. 16 SEM micrographs of the Ni-P/Ni-B-W coatings before and after the heat treatments showed the formation of typical spherical nodular structures (Figure 2).…”
Section: Discussionmentioning
confidence: 99%